2009
DOI: 10.1002/jmri.21818
|View full text |Cite
|
Sign up to set email alerts
|

Added value of diffusion‐weighted imaging in the MRI assessment of perilesional tumor recurrence after chemoembolization of hepatocellular carcinomas

Abstract: Purpose: To investigate the additional value of diffusionweighted imaging (DWI) in the MRI assessment of perilesionally recurrent hepatocellular carcinomas (HCCs) after transcatheter arterial chemoembolization (TACE). Materials and Methods:For gadopentetate dimeglumineenhanced multiphasic dynamic images with precontrast T1-and T2-weighted images of 23 patients treated with TACE, two radiologists independently sorted the confidence levels for the presence of a viable tumor in the vicinity of the treated lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…Specifically, an increase in ADC values was proposed as a noninvasive measurement of tumor necrosis after treatment (14,35,36). The tumor ADC value may substantially change as early as 1-2 weeks after therapy (37).…”
Section: Survival Analysesmentioning
confidence: 99%
“…Specifically, an increase in ADC values was proposed as a noninvasive measurement of tumor necrosis after treatment (14,35,36). The tumor ADC value may substantially change as early as 1-2 weeks after therapy (37).…”
Section: Survival Analysesmentioning
confidence: 99%
“…It improves MR detection of HCCs, particularly in lesions smaller than 2 cm [85], with sensitivities of 84–98% compared to 76–85% for multiphasic MRI alone [8688]. Potentially, objective measurement of the apparent diffusion coefficient (ADC) may allow for distinction between the different tumour grades [89, 90].…”
Section: Imaging Diagnosismentioning
confidence: 99%
“…It can be combined with SPIO-enhanced MRI, raising sensitivity from 66% to 70%, while maintaining high specificity of 98% [91]. DW MRI also shows potential for assessment of treatment response to local ablative therapies [88, 92]. Its role in the diagnostic algorithm is not certain at this point, although, given the promising results and its ease of implementation in routine clinical practice (due to fast acquisition times, no needs for additional hardware and ease of interpretation), incorporation into future guidelines is anticipated.…”
Section: Imaging Diagnosismentioning
confidence: 99%
“…Mannelli et al [91] did not report differences between conventional MRI sequences and DWI for the assessment of post-TACE necrosis, although enhancement decrease on MRI subtraction images was more significantly correlated with pathological findings than ADC increase. Although quantitative analysis of diffusion restriction appears to be of value in assessing response to TACE, visual analysis seems to be less accurate: Goshima et al [92] reported that DW images were significantly less sensitive than contrast-enhanced images in detecting residual/recurrent tumor after TACE, and Yu et al [93] reported that the addition of DW images to contrastenhanced images reduced specificity and diagnostic accuracy in detecting perilesional recurrence. Probably, the presence of treatment-induced granulation tissue is the cause of DWI false positives.…”
Section: Primary Liver Tumorsmentioning
confidence: 99%